Parental Social Support and Academic Resilience in Final Year Students Who are Compiling Their Final Assignments - Desri Marianty Tanga Wila; Arthur Huwae (Bisma The Journal of Counseling, 2023)
When completing their final assignments, final-year students face various obstacles. The obstacles encountered can impact not only graduation but also psychological problems. To face existing obstacles, final-year students must have good academic resilience. One factor that can shape academic resilience is parental social support. Therefore, this study examines the relationship between parental social support and academic resilience in final-year students working on their final assignments. The research method used is quantitative correlational with Spearman's Rho correlational design. Two hundred-one final-year undergraduate students from the 2016-2020 class working on their final assignments participated in this research using a purposive sampling technique. The research measurements used the Parental Social Support Scale (α = 0.923) and Academic Resilience (α = 0.891). The research results prove that the hypothesis that parental social support is positively related to academic resilience (r = 0.326 and sig. = 0.000) is accepted. These results indicate that parental social support is one of the factors related to the academic resilience of final-year students working on their final assignments. This means that an increase or decrease in parental social support is related to an increase or decrease in academic resilience.